Foreword - Mary P. McKeown-Moak (Educational Considerations, 2003)
This edition of Educational Considerations is devoted to the issues impacting on higher education at the beginning of the 21st century: declining revenues from all sources; increasing demands for accountability; increasing costs leading to increases in tuition and fees; enrollment management; and the changing role of state governments.